Legislative Intervention in Corporate Governance is Not a Necessary Response to Citizens United v. Federal Election Commission - Yoder, Stephen A. (Journal of Law and Commerce, 2010)
Few recent decisions of the United States Supreme Court have created quite the stir as did Citizens United v. Federal Election Commission. One reason the opinion had such an effect is that it contains a smorgasbord of business-related legal and political issues, including issues relating to election law, ethics, social responsibility, stare decisis, judicial review, selection of Supreme Court Justices, the definition of free speech, and corporate “personhood” for purposes of the First Amendment. Perhaps surprising for a case involving a lawsuit brought by a nonprofit public advocacy organization against the federal agency charged with enforcing federal election laws, the opinion also ventures into one of the most important current issues in corporate governance, the role of shareholders in the business and affairs of a corporation.